2017
DOI: 10.3389/fnut.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

Non-Conscious Effect of Food Odors on Children’s Food Choices Varies by Weight Status

Abstract: ObjectiveFood cues are omnipresent in the daily environment and may influence eating behavior even non-consciously. An increased reactivity to food cues, such as food odors, has been shown to be correlated with obesity in children. The objective of this study is to investigate whether the non-conscious influence of food odors on children’s food choices varies by their weight status.MethodsSeventy-four children, of whom 29 were obese, took part in this study. The children performed a food choice intention task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…In an earlier study, we found that implicit priming of olfactory food cues had differentiated effects: individuals with obesity were more vulnerable to a non-attentively perceived pound cake odour in their bottom-up processing of food cues [23]. For individuals with overweight in the present study, the effect of the pear odour is consistent with a study by Marty & al [19] in which olfactory pear and pound cake primes had differentiated effects when they were non-attentively perceived by children with overweight. Indeed, these children were more prone to choose fruit in a forced-choice task when they were non-attentively primed with a pear odour.…”
Section: Differences In Vulnerability To Food Cues In Individuals Witsupporting
confidence: 92%
See 3 more Smart Citations
“…In an earlier study, we found that implicit priming of olfactory food cues had differentiated effects: individuals with obesity were more vulnerable to a non-attentively perceived pound cake odour in their bottom-up processing of food cues [23]. For individuals with overweight in the present study, the effect of the pear odour is consistent with a study by Marty & al [19] in which olfactory pear and pound cake primes had differentiated effects when they were non-attentively perceived by children with overweight. Indeed, these children were more prone to choose fruit in a forced-choice task when they were non-attentively primed with a pear odour.…”
Section: Differences In Vulnerability To Food Cues In Individuals Witsupporting
confidence: 92%
“…The result of the priming effect seen here is congruent with the results of previous studies [19,23]. In an earlier study, we found that implicit priming of olfactory food cues had differentiated effects: individuals with obesity were more vulnerable to a non-attentively perceived pound cake odour in their bottom-up processing of food cues [23].…”
Section: Differences In Vulnerability To Food Cues In Individuals Witsupporting
confidence: 91%
See 2 more Smart Citations
“…In other words, it may be possible to orientate children's food choices by making choice option more or less salient in children's mind, by manipulating cues in the environment that are likely to "prime" mental representation of these foods (Chambaron et al 2015;Gaillet et al 2013). Following on this idea, one study attempted to prime mental representations of healthy versus unhealthy foods in children by using olfactory primes (respectively, a pear odor to prime "healthy foods" and a pound cake odor to prime "unhealthy foods") and evaluated whether the presence of these olfactory primes would be associated with different choices for healthy versus unhealthy foods and whether the effect of the olfactory primes on food choices would be different in children with or without overweight (Marty et al 2017a). In children with obesity, the fruity odor increased the likelihood of a fruit to be chosen compared to the noodor condition, while the fatty-sweet odor had no effect on food choice.…”
Section: School Age: a Curious Autonomous Eater Still Framed By Parementioning
confidence: 99%